Level of Satisfaction of Selected Teaching Personnel on the Wellness Programs of Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employee wellness programs are initiatives companies use to improve the health of theirworkers but aim to reduce health-related absenteeism and increase employee productivity.Wellness programs promote employee’s well-being. Bestlink College of the Philippines hasdifferent programs that help employees relieve stress at work because the hard work of theemployees also reflects the image of Bestlink College of the Philippines.According to the study, the majority of respondents were female and between the ages of31-40. The majority of them had 2-5 years in service, with 21 teaching personnel each. Themajority of them were from the BSED department, and the majority of respondents were full-time teachers. It also reveals that the teaching personnel are satisfied with the wellnessprograms of the Bestlink College of the Philippines.At the end of the study, the researcher suggests maintaining the wellness of the employeesfor satisfaction. And retain talent by promoting more wellness programs like stressmanagement programs, yoga sessions, and gym membership.
Keywords: Business Administration